2017
DOI: 10.5489/cuaj.4584
|View full text |Cite
|
Sign up to set email alerts
|

The management of mixed urinary incontinence in women

Abstract: Mixed urinary incontinence is a common diagnosis among women with urinary leakage and is often present in women who are unable to characterize their incontinence. Research and optimized clinical treatment of these patients is limited by the challenges in objectively defining and stratifying this population. The evaluation of these patients should follow the same general principles as any assessment of any women with incontinence; however, it is essential to define whether urge or stress incontinence is the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Guidelines and recommendations for mixed urinary incontinence treatment caution that surgery could worsen the urgency component. 5,6,8 Observational data supporting that midurethral sling surgery remains effective for treating the stress component exists. 9 However, limited studies have evaluated approaches to improve urgency incontinence outcomes after midurethral sling among women with mixed incontinence.…”
mentioning
confidence: 99%
“…Guidelines and recommendations for mixed urinary incontinence treatment caution that surgery could worsen the urgency component. 5,6,8 Observational data supporting that midurethral sling surgery remains effective for treating the stress component exists. 9 However, limited studies have evaluated approaches to improve urgency incontinence outcomes after midurethral sling among women with mixed incontinence.…”
mentioning
confidence: 99%
“…7 Non-surgical treatment is considered as the first-line treatment and includes weight loss, behaviour modification, pelvic floor muscle training, reduced fluid intake, caffeine moderation, biofeedback, anti-incontinence devices, and pharmacological treatment. 2,7,8 While, surgical treatment is an option for women with stress-predominant MUI or with equal components of SUI and UUI, and not responding to nonsurgical interventions. These includes urethral bulking agents, retropubic suspensions, bladder neck slings, or midurethral slings.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…These includes urethral bulking agents, retropubic suspensions, bladder neck slings, or midurethral slings. 2,8 Among these surgical methods, midurethral sling (MUS) procedures such as transobturator tape (TOT) and tension-free vaginal tape (TVT) are most widely used. 2 Some studies have reported that TOT is more promising to result in total resolution of MUI, due to its less obstructive nature.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…It is characterized by a combination of stress and urge symptoms in the same patient. It has a major effect on a woman’s quality of life (QOL) [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%